KONTRIBUSI KEKUATAN OTOT LENGAN DAN KESEIMBANGAN TERHADAP KEMAMPUAN PASSING ATAS BOLAVOLI (Studi Ekstrakurikuler Bolavoli SMP 2 Kampar Utara) - nuradila putri, nanda nuradila putri (Pusat Pengembangan Olahraga Universitas Pahlawan, 2024)
Not all the players can do the upper passing technique well. This technique the requires the element or other factors. The player must have strong arm muscle, strong hand squeeze muscle, strong leg mscle and the balance of body. So, they can do the passsing well and on target. The arm muscle strenght is needed because it is used for the ball to pass on target. The hand should be tightly in doing the upper passing, the hand squeeze muscle is very necessary. So the passing can be done well. The leg muscle strenght is needed as a foot defense or squatt. The balance is necessary to reach the ball. So we can move freely. The researcher uses the correlation study in this research. Correlation study means the data consist of some variables; is how strong the variables that occured; in other word, is necessary to determine the degree beetwen variables. Based on the result that have been conducted, the arm muscle strenght is 26.6%, and balance is 29,7% to the upper passing ability. The precentage of correlation between the value and upper passing ability is influenced by th score of arm muscle strenght, hand squeeze muscle strenght, leg muscle stregnht and the balance; it’s about 14%. whereas for 86%% is influnced by other factor which is not included in this research. Keywords: Muscle Strength, Hand Squeeze Muscle Strength, Leg Muscle Strength, Balance, Upper Passing, Volleyball